The emission-inequality nexus across stages of development - Francesco Lamperti; Elisabetta Palagi; Tommaso Perniola (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2025)
Does a more unequal society emit more CO2? The nexus between carbon emissions and income inequality has been at the core of a vast literature, which has yielded conflicting results. Leveraging panel econometric techniques, we provide robust evidence of a non-linear relationship that depends on the structural composition of the economy. Specifically, we document a positive association between income inequality, measured with five different indicators, and per capita carbon emissions in highly tertiarized countries. In contrast, the relationship in non-service-intensive economies turns negative. We provide evidence for plausible mechanisms mediating this non-linear association: the carbon footprint of the richest individuals -particularly when linked to investment- and the employment share in industry are key factors underlying the observed patterns. Our results point to the stage of "development" as a crucial factor shaping the emission-inequality nexus. Indeed, it helps identify countries for which fighting inequality comes with climate-related benefits.
Keywords: C23; D31; Q50; Q54; 330; income inequality; climate change; emissions; carbon; mitigation